The impact of promotion in franchising - Iva Buljubašić; Marta Borić (Ekonomski Vjesnik, 2014)
Franchising is a model of company growth, which significantly reduces uncertainty in the riskiest stages of growth: business start–up and growth phase. The impact of promotion in franchising has not been investigated in relevant literature. Therefore, this paper examines the impact of promotion on franchising through unconventional marketing on the example of private company X which is the main context of the present study. This private company X was chosen as a relevant example because it was selected in 2012 as one of the most successful Croatian franchisee companies in the segment of automotive industry and also because of the quality of service. The results show that the most successful promotional tool is “word of mouth” that attracts the largest number of clients. However, it must be emphasized that conventional marketing is very important, too, because it contributes to the visibility of the company. Conventional marketing is a diverse field which includes many forms of advertising like print, broadcast, direct mail, telemarketing etc. and is still widely recognized by the audience.